Classification of external stakeholders in green supply chain management - Karimi, Asrin; Abdul Rahim, Khalid (Elsevier, 2015)
The increasing importance of environmental issues requires efforts in different area of research and application. Green Supply Chain Management (GSCM) offers great potentials for the improvement of ecological performance of manufacturers. The purpose of this paper is to explore the stakeholders’ pressures on green supply chains, and to develop a taxonomy framework that can be used for green supply chain decision makers based on the characteristic dimensions for the green supply chain. The taxonomic framework is developed through (i) analysis of different dimension of green supply chain found in existing empirical work or case studies recorded in the literature, (ii) identification of key stakeholders’ pressures that influence green supply chain management initiative.